Allelic Impacts of TaPHS1, TaMKK3, and Vp1B3 on Preharvest Sprouting of Northern Great Plains Winter Wheats. Issue 1 (1st January 2019) - Vetch, Justin M.; Stougaard, Robert N.; Martin, John M.; Giroux, Mike
Abstract : Preharvest sprouting (PHS) of bread wheat ( Triticum aestivum L.) is a common problem that can lead to negative economic impacts arising from yield loss and undesirable end‐use quality. Twenty‐one winter wheats adapted to northwestern Montana were grown over two field seasons and used to assess three loci observed in previous studies to have moderate to large impacts on PHS. The main goal was to validate the usefulness of TaPHS1‐3A (a Mother of Flowering Time ‐like gene), TaMKK3‐4A (a mitogen‐activated protein kinase kinase 3), and Vp1‐1B ( Viviparous 1 ) in breeding for modified dormancy before harvest, as well as to determine their potential relationships to agronomic and seed traits, specifically, falling number and α‐amylase concentrations. Variation in PHS susceptibility across entries ranged from 0% sprout (fully dormant) to 95% sprout (fully nondormant) after 7 d of wetting. Most entries showed an intermediate level of sprouting susceptibility ranging between 10 and 50% sprouted. Alleles previously reported to impact dormancy were found for all three genes but TaPHS1 was the only locus found to be significantly associated with PHS. It is unclear whether variation caused by TaPHS1 may be masking the effects of the other loci, but it is evident that TaPHS1 could be used in a breeding program to modify the level of seed dormancy in winter wheat before harvest.